PENGARUH VISKOSITAS, LAJU ALIRAN, DAN VOLUME PADA SYRINGE PUMP BERBASIS MIKROKONTROLER - M Arief Dermawan Mailani, (2020)
Syringe pumps are only used for medical equipment with high prices in the future, it does not rule out the possibility that syringe pumps can be used in various fields to inject fluids that can be regulated for accuracy, thereby increasing efficiency in industries that do not require sterile materials and materials. For this reason, we took the initiative to make a microcontroller-based syringe pump. The purpose of this study is to test the function of the tool to the variation of vososity, flow rate and volume to determine the effect of viscosity, flow rate, and volume on the syringe pump injection process. This research was conducted using a Randomized Group Design (RBD) method with 3 factors and 3 repetitions. The result is that the syringe pump is quite good in injecting fluid in the variation of these factors with the smallest value of 29.76 ml in the variation of the 30 ml volume factor and 49.7 in the 50 ml volume factor variation.